Comparative study to assess the outcome of surgical management of humerus shaft fracture: anterior bridge plating versus humerus intramedullary nailing - Arora, Gagan; Varshney, Anurag; Singh, Surya V.; Bajaj, Kanwal (International Journal of Research in Orthopaedics, 2025)
Background: Aims and objectives of the study were to assess the outcomes of surgical management of humeral shaft fractures using anterior bridge plating (ABP) versus humeral intramedullary nailing (HIN) in terms of functional recovery and complication rates. Methods: A prospective observational and interventional study was conducted from July 2022 to June 2024 at the tertiary care hospital. Sample size of 40 patients was taken. Results: The study included 40 patients, with similar demographics between the groups. We divided the cases in two groups (HIN group A and ABP group B). Out of 40 patients, 23 were male and 17 were female. Postoperative follow-up at 24 weeks indicated improved functional outcomes assessed by UCLA score system for the ABP group B, with 65% achieving excellent, 25% good, 10% fair and 0% poor as compared to 55% good, 30% fair, and 15% poor in the HIN group A. In terms of complication, in the group A, one (5%) patient had radial nerve palsy, 3 (15%) nonunion, 1 (5%) delayed union and 1 (5%) superficial infection whereas in group B, no radial nerve palsy and nonunion, but 3 (15%) patients have delayed union and 1 (5%) superficial infection. Conclusions: Anterior bridge plating demonstrated superior functional recovery compared to intramedullary nailing in patients with humerus shaft fractures, suggesting it may be the preferred surgical option for better patient outcomes but no significant difference in complications like delayed union and infection. Further research is warranted to validate these findings and refine treatment guidelines.